2011
DOI: 10.2220/biomedres.32.37
|View full text |Cite
|
Sign up to set email alerts
|

Human bone marrow adipocytes support dexamethasone-induced osteoclast differentiation and function through RANKL expression

Abstract: The TNF-family molecule, Receptor Activator of Nuclear factor κ B Ligand (RANKL) is known as a key regulator for bone remodeling, and is essential for the development and activation of osteoclasts. In this study, we examined the regulation of RANKL in primary human bone marrow adipocytes and the relationship between bone marrow adipocytes and bone metabolism. RANKL expression and the RANKL/osteoprotegerin (OPG) mRNA ratio in marrow adipocytes increased following dexamethasone treatment. In co-cultures of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Halade et al (16) reported that OPG secretion decreased and RANKL expression increased in osteoblasts stimulated with adipocyte-secreted factors. By contrast, Goto et al (20) demonstrated that adipocyte-secreted cytokines upregulated RANKL mRNA expression in osteoblasts, consistent with osteoclast differentiation in vitro. These observations are in agreement with those of this study and demonstrate that adipocytes increase osteoclastogenesis via the OPG/RANKL/RANK system in the bone microenvironment.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Halade et al (16) reported that OPG secretion decreased and RANKL expression increased in osteoblasts stimulated with adipocyte-secreted factors. By contrast, Goto et al (20) demonstrated that adipocyte-secreted cytokines upregulated RANKL mRNA expression in osteoblasts, consistent with osteoclast differentiation in vitro. These observations are in agreement with those of this study and demonstrate that adipocytes increase osteoclastogenesis via the OPG/RANKL/RANK system in the bone microenvironment.…”
Section: Discussionmentioning
confidence: 92%
“…Oshima et al (19) demonstrated that adiponectin induced by cytokines secreted by adipocytes directly suppresses bone-resorption activity by inhibiting osteoclastogenesis. However, observations of Goto et al (20) demonstrate that primary human bone marrow adipocytes promote osteoclast differentiation and activities. Leptin, an adipocyte-derived cytokine, has been found to function as a negative regulator of bone mass in a mouse model (21).…”
Section: Discussionmentioning
confidence: 97%
“…Considering that BMSCs are the precursors of osteoblasts, adipogenesis in the bone marrow limits the pool of osteoblasts, however, recent studies have indicated that it also potentiates bone metabolism through secretion of the factors such as insulin, insulin-like growth factor, and leptin (5,17,18,24). In fact, our previous observations demonstrated that bone marrow-derived adipocytes expressed the RANKL gene transcripts, whose level was up-regulated by TNF-α and dexamethasone (10,11,15). Therefore, in the present study, we aimed to examine the role of adipogenic conversion of BMSCs in osteoclastogenesis in vitro, focusing on the production of RANKL.…”
Section: Discussionmentioning
confidence: 97%
“…Total protein concentration was determined by the BCA protein assay (Pierce, Rockford, IL). Proteins (8 or 16 μg) were electrophoresed through an SDSpolyacrylamide gel and were electrophoretically is mediated by augmented expression of RANKL in adipocytes (10,11,15). These lines of evidence also suggest that adipogenic differentiation of BMSCs in the bone marrow might stimulate osteoclastogenesis.…”
mentioning
confidence: 98%
“…In the bone marrow space, there is a large quantity of mature adipocytes that are possible candidates for adipokine secretion. Considering the enclosed nature of the bone marrow space, intramedullary adipocytes may be involved in bone metabolism, as we previously reported that bone marrow adipocytes express receptor activator of nuclear factor kappa-B ligand (RANKL) and support osteoclast differentiation (5,8). Plasminogen activator inhibitor-1 (PAI-1), one of the adipokines secreted by adipocytes (1), suppresses fibrinolysis by binding tissue-type plasminogen activator (t-PA), and a relationship between PAI-1 and thrombosis or hypercoagulation has been suggested.…”
mentioning
confidence: 99%